A note on quality of a firm's exports and distance to destination countries: First evidence from Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
This note uses a tailor-made new data set to investigate for the first time the link between the quality of a firm's exports and the distance to destination countries for Germany. To anticipate the most important result, it is shown that the quality of exported goods and the distance to destination countries are not statistically positively correlated.
Keywords: F14; 330; Exports; export quality; distance; Germany